Anti-inflammatory effects of compounds from Polygonum odoratum - Okonogi S. (2017)
Polygonum odoratum is an edible plant traditionally used as an antidiabetic, antimicrobial, anti-inflammatory, and antitumor agent in Asia. The aim of the study was to evaluate the anti-inflammatory effect of P. Odoratum and the isolation and characterization of its main fractions. Extracts of the aerial parts were tested for anti-inflammatory activity as indicated by a change in the cytokine secretion in lipopolysaccharide-stimulated macrophages. After separation of the extract by reversed-phase high-performance liquid chromatography, the anti-inflammatory activity of the fractions was determined. Furthermore, the two main fractions were identified by nuclear magnetic resonance spectroscopy ( 1 H- and 13 C-NMR). The ethanolic extract significantly reduced IL-6 secretion (IC 50 25 μg/mL). The two main fractions (5 and 7) significantly decreased IL-6 production with an IC 50 of 102 μM (5) and 77 μM (7), respectively, and were identified as scutellarein-7-glucoside (5) and quercitrin (7). Since inflammation plays a major role in various diseases with high prevalence globally, it may be of importance that P. Odoratum and its main constituents scutellarein-7-glucoside and quercitrin can be used as either an alternative or complementary treatment. Additionally, both are glycosides and their activity may be enhanced tremendously by deglycosylation by the gut microbiota.